Business modeling and software design : 6th International Symposium, BMSD 2016, Rhodes, Greece, June 20-22, 2016, revised selected papers /: 6th International Symposium, BMSD 2016, Rhodes, Greece, June 20-22, 2016, revised selected papers. (2017) - Unknown
No abstract available